Clifford the big red dog [videorecording (DVD)] - Whitehall, Jack, 1988-; Camp, Darby, 2007-; Hale, Tony; Guillory, Sienna, 1975-; Grier, David Alan, 1956 June 30-; Wong, Russell, 1963-; Thompson, Kenan; Cleese, John (Paramount Home Entertainment, 2022)
When middle-schooler Emily Elizabeth meets a magical animal rescuer who gifts her a little, red puppy, she never anticipated waking up to find a giant ten-foot hound in her small New York City apartment. While her single mom is away for business, Emily and her fun but impulsive uncle Casey set out on an adventure that will keep viewers on the edge-of-their-seats as the heroes take a bite out of the Big Apple.